2016
DOI: 10.18632/oncotarget.8528
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of PD-L1 and PD-L2 copy number gains in non-small-cell lung cancer

Abstract: New reliable biomarkers are needed to predict the response to immune checkpoint inhibitors against programmed death-1 (PD-1) and its ligand (PD-L1), because PD-L1 expression on tumor cells has limited power for selecting patients who may benefit from such therapy. Here we investigated the significance of PD-L1 and PD-L2 gene copy number gains using fluorescence in situ hybridization as well as PD-L1 and PD-L2 expression in 654 patients with resected non-small-cell lung cancer. The prevalence of PD-L1 amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 56 publications
7
104
3
Order By: Relevance
“…Although the microarray data suggests slightly higher expression of PD-L2, another ligand for PD-1, in HCC4006ER cells, the expression level of PD-L2 is lower in lung cancers [43] and the role of PD-L2 as a predictive biomarker for anti-PD-1/PD-L1 therapy is currently unclear. We have shown that HCC4006ER cells were insensitive to anti-microtubule agents that are often used as cytotoxic agents in non-small cell lung cancers [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the microarray data suggests slightly higher expression of PD-L2, another ligand for PD-1, in HCC4006ER cells, the expression level of PD-L2 is lower in lung cancers [43] and the role of PD-L2 as a predictive biomarker for anti-PD-1/PD-L1 therapy is currently unclear. We have shown that HCC4006ER cells were insensitive to anti-microtubule agents that are often used as cytotoxic agents in non-small cell lung cancers [28].…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of PD-L1 expression in tumor cells is complex and affected by several mechanisms including: PD-L1 genomic gains [14], structural variations of the 3’ region of the PD-L1 gene [15], oncogenic signaling activation such as AKT serine/threonine kinase (AKT) – mechanistic target of rapamycin (mTOR) pathway [16], Janus kinase (JAK) – signal transducer and activator of transcription (STAT) pathway [17], and mitogen-activated protein kinase 1 (MAPK1) – Jun proto-oncogene, AP-1 transcription factor subunit (JUN) pathway [18]. In addition, PD-L1 expression in tumor cells is influenced by a variety of factors such as release of IFN-gamma from T cells in the tumor microenvironment in vivo [19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study demonstrated a significant difference in overall survival between PD-L1 positive and negative patients (7·2 years versus 14·0 years, respectively). [29] For this reason, PD-L1 amplification assays may be useful predictive biomarkers that may one day replace, or be performed in addition to, PD-L1 IHC.…”
Section: Dna Level Changesmentioning
confidence: 99%
“…Elevated expression of PD-L1 has been found to represent an adverse prognostic biomarker in NSCLC [126]. PD-L1 can be up-regulated by IFN-γ produced by tumor-infiltrating T cells thus promoting the progression of cancer [127].…”
Section: The Pd-1 Protein and Its Ligandsmentioning
confidence: 99%